2007
DOI: 10.1016/j.atherosclerosis.2006.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and coronary heart disease risk in the PRIME study

Abstract: Introduction: Despite recent meta-analyses suggesting that homocysteine is an independent predictor of coronary heart disease (CHD), there is debate regarding whether elevated homocysteine may be deleterious only in the presence of other risk factors, with which it acts synergistically to exert a multiplicative effect on CHD risk, emerging only as a CHD predictor in patients with pre-existing risk factors.The Prospective Epidemiological Study of Myocardial Infarction (PRIME) Study is a multicentre prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that 85.2% of Korean AP smoke 20 cigarettes/day or more, and 85.4% of AP smoked more than one pack of cigarettes/day for the last month 1. Since elevated Hcy strongly correlates with smoking and low blood folate levels were found in the PRIME case-control study, Hcy levels might be a secondary risk factor to low blood folate and smoking 22. Elevated Hcy may also be involved in hypertension because it is associated with impaired endothelial function due to the generation of oxidative stress, VCAM-1 and reduction of NO bioavailability 23,24.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that 85.2% of Korean AP smoke 20 cigarettes/day or more, and 85.4% of AP smoked more than one pack of cigarettes/day for the last month 1. Since elevated Hcy strongly correlates with smoking and low blood folate levels were found in the PRIME case-control study, Hcy levels might be a secondary risk factor to low blood folate and smoking 22. Elevated Hcy may also be involved in hypertension because it is associated with impaired endothelial function due to the generation of oxidative stress, VCAM-1 and reduction of NO bioavailability 23,24.…”
Section: Discussionmentioning
confidence: 95%
“…A positive association was demonstrated between plasma homocysteine levels and extent of atherosclerosis [85, 86], as well as the risk of hypertension [87], stroke [85,86,87,88], carotid artery disease [89, 90], CHD [87, 91, 92], PAD [93, 94] as well as MI [95, 96]. …”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Despite previous meta‐analyses suggesting that homocysteine is an independent risk factor for atherosclerosis and other cardiovascular diseases (CVD) [1], recently there has been a debate regarding the role of homocysteine in the development of CVD [2]. However, evidence indicates that an elevated plasma homocysteine level is still considered as an important risk factor for CVD, at least in high‐risk patients [3,4]. It has been recently reported that total plasma homocysteine is a strong predictor of recurrence of unstable angina [5].…”
Section: Introductionmentioning
confidence: 99%